Prevalence and Causes of Myocardial Infarction with Non-Obstructive Coronary Arteries in a Contemporary Cohort of Patients with Suspected Myocardial Infarction - Dominik Dees (MDPI AG, 2021)
Background: A significant proportion of patients presenting with acute myocardial infarction (MI) has no coronary obstruction at coronary angiography and no other obvious non-coronary pathophysiology causing MI. These patients are classified as MI with non-obstructive coronary arteries (MINOCA). Data on incidence and predictors of MINOCA are still limited. Methods: This study enrolled patients presenting symptoms suggestive of MI and undergoing a comprehensive cardiac work-up including an early invasive strategy. Patients with non-obstructive coronary arteries and without other obvious reasons for MI were scheduled for further work-up including magnetic resonance or intraluminal imaging. MINOCA was diagnosed according to the current European Society of Cardiology guidelines. Results: From the 1532 patients enrolled, 730 had available coronary imaging and 546 were diagnosed with MI. No significant coronary obstructions were found in 117 patients with MI. After the exclusion of 6 patients with acute myocarditis or takotsubo-syndrome as well as 88 with type II MI, 23 patients were diagnosed with MINOCA (4% of all MIs). Among these 23 patients, the most common etiology of MINOCA was thromboembolic events followed by coronary spasm. Female sex, the absence of hypercholesterolemia, and a normal left-ventricular ejection fraction were independently predictive for MINOCA compared to patients with other causes of MI. Conclusion: More than 20% of patients presenting with acute MI showed no significant coronary obstruction. About 4% of these patients were diagnosed with MINOCA. Female sex, a lower cardiovascular risk profile, and normal left-ventricular function were predictive for MINOCA.